The role of women’s resources in the prediction of intimate partner violence revictimization by the same or different aggressors - Bellot, Ana; Izal, María; Montorio, Ignacio (Frontiers in Psychology, 2022)
The literature studying the characteristics associated with revictimization in Intimate Partner Violence (IPV) is heterogeneous and inconclusive. The absence of studies on the role of the emotional variables of the victims and the failure to distinguish revictimization by the same or different aggressors are two of the main limitations in this area of research. The aim of this work was to study the relative contribution of the material, social, and emotional resources available to IPV victims in predicting revictimization by the same or different perpetrators. The sample consisted of 290 women registered in the city of Madrid who had filed at least one police report for intimate partner violence. The material resources of the victims were evaluated through their level of monthly income and employability status, the social resources through perceived social support, and the emotional resources through emotional regulation and coping strategies. Hierarchical multinomial logistic regression models were estimated to predict single-offender victimization (SRV), same-offender revictimization (VSRSA), and multiple-offender revictimization (VSRDA). The results revealed that: (1) differentiating between revictimization by the same and different aggressors improved the fit of the model by 50.8% compared to when only differentiating between victimized and revictimized women; (2) material resources had no significant weight in the prediction of any type of revictimization; (3) SRV women had more social support than VSRDA women (ExpB = 1.027; p < 0.011); (4), those victims who had made several reports to the authorities of violence by different aggressors (VSRDA), had worse emotional regulation than those victims who had made a single report to the authorities (VSRs; ExpB = 2.934; p < 0.026); and (5) VSRDA obtained the worst mental health indexes and they used more coping strategies based on positive reappraisal than the VSR women (ExpB = 0.863; p < 0.009) and those victims with several reports by the same aggressor (VSRSA; ExpB = 0.891; p < 0.028). These results show that being a victim of several episodes of intimate partner violence by different aggressors should be understood as a form of revictimization of great severity associated with worse emotional regulation and less social support.